Peripheral blood flow disorders and its role in the development of diabetic peripheral polyneuropathy in children - Spilnyk, M. S.; Lezhenko, G. O.; Zakharchenko, N. A.; Спільник, М. С.; Леженко, Геннадій Олександрович; Захарченко, Наталія Анатоліївна (My University, 2025)
Objective — to evaluate the state of blood supply to the lower extremities in children with type 1 diabetes mellitus by the results of the ankle brachial index and to detect latent peripheral circulatory disorders in the development of diabetic peripheral polyneuropathy. Materials and methods. The study included 103 children (mean age (13.57 ± 0.24) years) with type 1 diabetes mellitus. Depending on the duration of the disease, two groups of patients were formed. Group 1 included 70 children with diabetes mellitus duration up to 5 years (mean duration (2.21 ± 0.16) years), group 2 consisted of 33 patients with diabetes mellitus duration over 5 years (mean duration (8.45 ± 0.41) years). The control group consisted of 33 children without carbohydrate metabolism disorders and neurological disorders. Diabetic peripheral polyneuropathy (DPP) was diagnosed in 47 (45.6 %) of 103 children with diabetes mellitus. The ankle brachial index (ABI) was determined by measuring systolic blood pressure in the upper and lower extremities sequentially. To determine the latent disorders of peripheral circulation, the measurement and calculation of the ABI was performed before and after exercise. Paired linear regression analysis was used to assess the relationship between the indicators. ROC analysis was performed to determine the effectiveness of the use of the ABI as a screening group for the development of DPP. To assess the risk of developing DPP in children, the odds ratio and its 95 % confidence interval were calculated. Мета роботи — оцінити стан кровопостачання нижніх кінцівок у дітей, хворих на цукровий діабет 1 типу, за величиною кісточково-плечового індексу та визначити роль його порушень у розвитку діабетичної периферичної полінейропатії. Матеріали та методи. Під спостереженням перебували 103 дитини (середній вік — (13,57 ± 0,24) року), хворих на цукровий діабет 1 типу. Залежно від тривалості захворювання сформовано дві групи пацієнтів: перша — 70 дітей із тривалістю цукрового діабету до 5 років (середня тривалість — (2,21 ± 0,16) року), друга — 33 пацієнти з тривалістю цукрового діабету понад 5 років (середня тривалість — (8,45 ± 0,41) року). Контрольна група — 33 дитини без порушень вуглеводного обміну та неврологічних відхилень. У 47 (45,6 %) хворих на цукровий діабет виявлено діабетичну периферичну полінейропатію (ДПН). Кісточково-плечовий індекс (КПІ) визначали шляхом вимірювання послідовно систолічного артеріального тиску на верхніх і нижніх кінцівках. Для визначення прихованих порушень периферичного кровообігу вимірювання та розрахунок КПІ проводили до та після фізичного навантаження. Для оцінювання залежності між показниками використовували парний лінійний регресійний аналіз. Для визначення ефективності застосування КПІ як скринінгу групи ризику розвитку ДПН проводили ROC-аналіз. Для оцінки ризику розвитку ДПН у дітей розраховували відношення шансів та його 95 % довірчий інтервал.
Порушення периферичного кровотоку та його роль у розвитку діабетичної периферичної полінейропатії в дітей
Keywords: diabetes mellitus; neurological condition; diabetic neuropathies; blood supply; ankle brachial index; ROC analysis; children; цукровий діабет; неврологічні ускладнення; діабетичні нейропатії; кровопостачання; кісточково- плечовий індекс; ROC -аналіз; діти